Demonstration of the bipartite nature of the genome of a single-stranded DNA plant virus by infection with the cloned DNA components. - Hamilton, W D (1983)
Linear double-stranded (ds)DNA, obtained by excision of the cloned A and B components of tomato golden mosaic virus (TGMV) from recombinant plasmids, was found to infect plants and to elicit symptoms identical to those obtained with TGMV or TGMV DNA. Progeny virus isolated from plants infected with cloned DNA was infective and indistinguishable from TGMV on the basis of (a) its circular single-stranded (ss)DNA genome, (b) its capsid polypeptide, (c) its particle morphology and (d) serological identity. Southern blot analysis of DNA extracted from cells infected with cloned DNA, or TGMV DNA, revealed the same intracellular ss and dsDNA species, represented in both A and B components, except for a subgenomic, possibly defective, DNA, which was not detected in infections with cloned DNA. Infection with cloned DNA was achieved when cloned A and B components were both present, but not with either cloned A or B components separately. TGMV is the first DNA virus for which unequivocal proof of a bipartite genome has been obtained.